Coordinating Supply Chains with a Credit Mechanism - Hu, F.; Xu, Honglei; Lim, C.; Sun, X. (InforMath Publishing Group, 2014)
This paper studies the supply chain coordination with a trade credit under symmetric and asymmetric information, where the retailer has an individual profit target from the business and the vendor is the decision-maker of the supply chain. We propose a coordination mechanism through credit contracts and show that a win-win outcome is achieved by redistributing the cost savings from coordination mechanism under certain constraints. Numerical examples are given to illustrate our results.